Prenatal diagnosis and genetic assessment of fetuses with single umbilical artery using chromosomal microarray analysis: a seven-year single-center retrospective study - Jianlong Zhuang; Nan Huang; Yu’e Chen; Jialing Wu; Xiaofang Ye; Chunnuan Chen (BMC Pregnancy and Childbirth)
Abstract Background The inherited causes behind fetuses with a single umbilical artery (SUA) are still poorly understood, largely because published studies are scarce. In the present research, efforts were made to uncover the genetic factors at play and to assess how SUA influences pregnancy outcome. Methods A retrospective review was performed on 5,014 pregnant individuals who underwent prenatal diagnostic testing between September 2017 and April 2023. Of these, 123 fetuses were found to have SUA. Amniocentesis was carried out in all affected cases, with samples analyzed via conventional karyotyping and chromosomal microarray analysis (CMA) to detect any chromosomal abnormalities. Results In the present study, four cases of chromosome aneuploid and two cases of chromosomal structural abnormalities were identified through karyotype analysis, with the chromosomal aberration detection rate being 4.88% (6/123). CMA confirmed every abnormality detected by conventional karyotyping and additionally identified 11 pathogenic copy number variants that had been missed. These novel findings included clinically significant conditions such as Wolf–Hirschhorn syndrome, Xq28 duplication syndrome, 16p13.3 duplication syndrome, 16p11.2 deletion syndrome, and 22q11.21 deletion syndrome. Overall, CMA provided an incremental diagnostic yield of 8.94% (11/123) beyond what karyotyping alone achieved (P = 0.001). Conclusion CMA markedly improved the identification of clinically relevant genetic alterations in fetuses presenting with a single umbilical artery, especially when the anomaly occurred in isolation. These findings highlight the value of CMA for uncovering the genetic contributors to SUA and advance the characterization of genotype–phenotype relationships in these cases.